The rise of a jazz art world - Lopes, Paul Douglas (Cambridge University Press, 2002)
This book presents a unique sociological vision of the evolution of jazz music in the twentieth century. Analysing organizational structures and competing discourses in the field of American music, Paul Lopes shows how musicians and the art world that grew around them transformed the meaning and practice of jazz.